Blocking mitochondrial pyruvate import in brown adipocytes induces energy wasting via lipid cycling. (4th December 2020) - Veliova, Michaela; Ferreira, Caroline M; Benador, Ilan Y; Jones, Anthony E; Mahdaviani, Kiana; Brownstein, Alexandra J; Desousa, Brandon R; Acín‐Pérez, Rebeca; Petcherski, Anton; Assali, Essam A; Stiles, Linsey; Divakaruni, Ajit S; et al.
Abstract: Combined fatty acid esterification and lipolysis, termed lipid cycling, is an ATP‐consuming process that contributes to energy expenditure. Therefore, interventions that stimulate energy expenditure through lipid cycling are of great interest. Here we find that pharmacological and genetic inhibition of the mitochondrial pyruvate carrier (MPC) in brown adipocytes activates lipid cycling and energy expenditure, even in the absence of adrenergic stimulation. We show that the resulting increase in ATP demand elevates mitochondrial respiration coupled to ATP synthesis and fueled by lipid oxidation. We identify that glutamine consumption and the Malate‐Aspartate Shuttle are required for the increase in Energy Expenditure induced by MPC inhibition in Brown Adipocytes (MAShEEBA). We thus demonstrate that energy expenditure through enhanced lipid cycling can be activated in brown adipocytes by decreasing mitochondrial pyruvate availability. We present a new mechanism to increase energy expenditure and fat oxidation in brown adipocytes, which does not require adrenergic stimulation of mitochondrial uncoupling. Synopsis: Inhibition of mitochondrial pyruvate import in brown adipocytes activates lipid cycling and increases energy expenditure even in the absence of adrenergic stimulation. In the absence of mitochondrial pyruvate entry, the TCA cycle receives carbons from glutamine to support beta‐oxidation. Genetic and pharmacological targeting of the mitochondrial pyruvate carrier (MPC) activates lipolysis and shifts metabolism towards fatty acid utilization. The activation of lipolysis induces an energy demanding cycle of esterification and triglyceride breakdown. The increase in energy expenditure is supported by glutamine oxidation and the activation of the malate‐aspartate shuttle. Abstract : Inhibition of mitochondrial pyruvate import in brown adipocytes activates lipid cycling and increases energy expenditure even in the absence of adrenergic stimulation. In the absence of mitochondrial pyruvate entry, the TCA cycle receives carbons from glutamine to support beta‐oxidation.